Ada Leonidivna Vorontsova (1934–2020) (PH Akademperiodyka, 2023)
Summary. In October 2020, passed away Ada Leonidivna Vorontsova, our esteemed colleague, well known specialist in experimental oncology, doctor of sciences in biology, professor, leading researcher, who devoted all her life to the R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, the National Academy of Sciences of Ukraine.